2016
DOI: 10.1111/jcpp.12637
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning and local‐global visual processing: candidate endophenotypes for autism spectrum disorder?

Abstract: Impaired cognitive flexibility, ideational fluency and response inhibition are strong candidate endophenotypes for ASD. They could help to delineate etiologically more homogeneous subgroups, which is clinically important to allow assigning ASD probands to different, more targeted, interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 60 publications
5
30
1
2
Order By: Relevance
“…This contrast might suggest that the unaffected sib-pair of AS may share more attention deficits than autism sib-pairs. Notably, these differences between unaffected siblings of autism and AS will be overlooked when the two conditions are grouped into one single category of ASD, supporting the importance of looking into the subgroups within the whole spectrum concerning the neurocognitive function [45]. In addition, our findings added to the current knowledge of the shared neurocognitive deficits between ASD probands and their unaffected siblings (e.g., executive function such as cognitive flexibility [4345] and planning [43, 47, 48]) by showing that a more fundamental function, attention performance (e.g., focused attention and sustained attention), may also be involved, particularly for siblings of AS probands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This contrast might suggest that the unaffected sib-pair of AS may share more attention deficits than autism sib-pairs. Notably, these differences between unaffected siblings of autism and AS will be overlooked when the two conditions are grouped into one single category of ASD, supporting the importance of looking into the subgroups within the whole spectrum concerning the neurocognitive function [45]. In addition, our findings added to the current knowledge of the shared neurocognitive deficits between ASD probands and their unaffected siblings (e.g., executive function such as cognitive flexibility [4345] and planning [43, 47, 48]) by showing that a more fundamental function, attention performance (e.g., focused attention and sustained attention), may also be involved, particularly for siblings of AS probands.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these differences between unaffected siblings of autism and AS will be overlooked when the two conditions are grouped into one single category of ASD, supporting the importance of looking into the subgroups within the whole spectrum concerning the neurocognitive function [45]. In addition, our findings added to the current knowledge of the shared neurocognitive deficits between ASD probands and their unaffected siblings (e.g., executive function such as cognitive flexibility [4345] and planning [43, 47, 48]) by showing that a more fundamental function, attention performance (e.g., focused attention and sustained attention), may also be involved, particularly for siblings of AS probands. Whether the attention deficits co-segregate with other neurocognitive functions (like the co-segregation of social cognition and executive function [74]) and how these deficits (e.g., higher response variability, lower vigilance) influence other neurocognitive functions (e.g., cognitive flexibility) in the siblings warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis [Geurts et al, 2014] of behavioral studies investigating response inhibition in ASD reported that individuals with ASD (mean age = 14.8 years) have more difficulties in inhibiting response impulses than typically developing controls, but results from studies using the Stroop-like task revealed more heterogeneity and inconsistent findings: the effect size was 0.31 for the Stroop-like task and the frank task, but dropped to 0.19 after excluding the Stroop-like task. Response inhibition deficits have also been found in people with autistic traits [Gökçen, Frederickson, & Petrides, 2016] and the relatives of ASD probands [Van Eylen et al, 2017], and thus are considered a candidate endophenotype for ASD [Van Eylen et al, 2017]. Besides, impaired response inhibition is also associated with ASD symptoms, such as inappropriate speech, stereotypical behavior, and unusual interests [Faja & Nelson, 2018;Mostert-Kerckhoffs, Staal, Houben, & de Jonge, 2015].…”
Section: Introductionmentioning
confidence: 99%